2009
DOI: 10.3899/jrheum.090694
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Is Common in Systemic Sclerosis: Results from the Canadian Scleroderma Research Group Database

Abstract: The risk for malnutrition in SSc is moderate and is associated with shorter disease duration, markers of GI involvement, and disease severity. Patients with SSc should be screened for malnutrition, and potential underlying causes assessed and treated when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 37 publications
11
76
2
3
Order By: Relevance
“…This tool combines body mass index (BMI) and weight loss measures. Using this tool, a study of 586 Canadian SSc patients showed that the risk of malnutrition in SSc was high, with more than 28% of patients being at medium or high risk of malnutrition [43]. Malnutrition was associated with more GI complaints, early disease, diffuse disease, and with possible malabsorption.…”
Section: Malnutrition In Sclerodermamentioning
confidence: 99%
See 1 more Smart Citation
“…This tool combines body mass index (BMI) and weight loss measures. Using this tool, a study of 586 Canadian SSc patients showed that the risk of malnutrition in SSc was high, with more than 28% of patients being at medium or high risk of malnutrition [43]. Malnutrition was associated with more GI complaints, early disease, diffuse disease, and with possible malabsorption.…”
Section: Malnutrition In Sclerodermamentioning
confidence: 99%
“…Malnutrition was associated with more GI complaints, early disease, diffuse disease, and with possible malabsorption. Interestingly, it was also associated with the physician global disease assessment of disease severity, which implies that there may be factors other than the GI tract that can predict malnutrition [43].…”
Section: Malnutrition In Sclerodermamentioning
confidence: 99%
“…43 Experts agree that all patients with SSc should be screened for malnutrition. 25 Weight loss is the most sensitive indicator of malnutrition and should be performed at regular intervals.…”
Section: Malnutritionmentioning
confidence: 99%
“…It is estimated that 30 % of SSc patients are at medium to high risk for malnutrition [81]. Patients should be aware of warning signs such as sudden weight loss and undergo yearly screening by a rheumatologist.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%